An Examination of the Nature of Trust in Buyer–Seller Relationships - Doney, Patricia M.; Cannon, Joseph P. (Journal of Marketing, 1997)
The authors integrate theory developed in several disciplines to determine five cognitive processes through which industrial buyers can develop trust of a supplier firm and its salesperson. These processes provide a theoretical framework used to identify antecedents of trust. The authors also examine the impact of supplier firm and salesperson trust on a buying firm's current supplier choice and future purchase intentions. The theoretical model is tested on data collected from more than 200 purchasing managers. The authors find that several variables influence the development of supplier firm and salesperson trust. Trust of the supplier firm and trust of the salesperson (operating indirectly through supplier firm trust) influence a buyer's anticipated future interaction with the supplier. However, after controlling for previous experience and supplier performance, neither trust of the selling firm nor its salesperson influence the current supplier selection decision.